Negotiating displacement: Acting and reacting against urban segregation in Bogotá, Colombia - Garzón Ramírez, Sonia (The Greek Review of Social Research, 2018)
Can public space in a global South city such as Bogotá be regenerated so as to become classless or neutral? To what extent and through which means can forcibly displaced people become claimants of their right to remain in Bogotá? Based on fieldwork carried out in Bogotá between April and December 2012, and drawing upon the experience of internally displaced people (IDPs), this article examines the achievements of the city’s regeneration. The displaced persons’ narratives bring to the fore the persistence of spatial scales organized along the lines of race, ethnicity and class, and show how the overlapping of these scales with the model of centralities that the city strives to implement, shapes IDPs’ subjectivities and participates in constructing their socio-spatial segregation. Therefore, I explore some practices through which this population circumvents cultural homogenization and mechanisms of segregation. Furthermore, drawing on the concept of acts of citizenship, I analyze some IDPs’ public demonstrations, and their networking with social movements. I argue that IDPs have achieved to disrupt a spatial order that worked to hide the plight of their displacement. In doing so, they have taken back the center of the city as the locus of political struggle and have positioned their right to remain in Bogotá at the center of the public debate.